Bureaucratic Complexity in Thailand: Transformation, Socio-Culture, Law, and Politics - Febriali Sahl, Dafiq; Abrillioga; Hilmi Syafiq (Jurnal Transformative, 2025)
This study aims to explain bureaucracy or public administration in Thailand as a system and organisation of public services and state policy implementation that is connected to various aspects: socio-cultural, legal, and political, especially in transformation efforts to improve public service performance. The data collection method for this study is a systematic literature review of books, journal articles, reports, and other sources over the past 10 years, classified into aspects of culture, politics, barriers and drivers of transformation, and law within Thailand's bureaucracy. Using the Public Administration Culture theoretical framework formulated by Guy Peters (2001) in his book The Politics of Bureaucracy, this research focuses on answering how Buddhist social culture, legal politics, and internal bureaucratic culture mutually influence bureaucratic transformation in Thailand? This study found that social culture, which is related to the social system, public participation, and Buddhism, as well as the legal framework, are social forces that construct the behaviour patterns and services of bureaucrats as part of Thai society. Similarly, political culture, which is related to power politics (the king, military, executive, and others) and the patterns of relationships between politicians and bureaucrats in both law and practice, also plays a role. In line with this, public administration culture also involves patrimonialism and clientelism practised in inter-bureaucratic relations as part of Thailand's broader political and public service system. In conclusion, bureaucracy in Thailand is a complex public service organisational system where its transformation efforts are shaped or influenced by multi-faceted interactions between socio-cultural, political, legal, and internal administrative factors.